Assembly and dynamics of proteins of the longitudinal and junctional sarcoplasmic reticulum in skeletal muscle cells - Cusimano, Vincenza (National Academy of Sciences, 2009)
The sarcoplasmic reticulum (SR) of skeletal muscle cells is a complex network of tubules and cisternae that share a common lumen delimited by a single continuous membrane. The SR contains longitudinal and junctional domains characterized by distinctive patterns of protein localization, but how SR proteins reach and/or are retained at these sites is not known. Here, we report that the organization of longitudinal SR proteins is a slow process characterized by temporally distinct patterns of protein localization. In contrast, junctional SR proteins rapidly and synchronously assembled into clusters which, however, merged into mature triadic junctions only after completion of longitudinal SR protein organization. Fluorescence recovery after photobleaching experiments indicated that SR organization was accompanied by significant changes in the dynamic properties of longitudinal and junctional proteins. The decrease in mobility that accompanied organization of the longitudinal SR proteins ank1.5-GFP and GFP-InsP3R1 was abrogated by deletion of specific binding sites for myofibrillar or cytoskeletal proteins, respectively. Assembly of junctional SR domains was accompanied by a strong decrease in mobility of junctional proteins that in triadin appeared to be mediated by its intraluminal region. Together, the data suggest that the organization of specific SR domains results from a process of membrane reorganization accompanied by the establishment of multiple protein–protein interactions with intrinsic and extrinsic cues.